Band alignment of Ga2O3/6H-SiC heterojunction - 常少辉 陈之战 黄维 刘学超 陈博源 李铮铮 施尔畏 (Chinese physics B, 2011)
A high-quality Ga2O3 thin film is deposited on an SiC substrate to form a heterojunction structure. The band alignment of the Ga2O3/6H-SiC heterojunction is studied by using synchrotron radiation photoelectron spectroscopy, The energy band diagram of the Ga2O3/6H-SiC heterojunction is obtained by analysing the binding energies of Ga 3d and Si 2p at the surface and the interface of the heterojunction. The valence band offset is experimentally determined to be 2.8 eV and the conduction band offset is calculated to be 0.89 eV, which indicate a type-II band alignment. This provides useful guidance for the application of Ga2O3/6H-SiC electronic devices.